Nilai Kearifan Lokal dalam Tradisi Anggara Kasih Patirtan Cabean Kunti - Eka Novi Setiani; Budi Waluyo; Prima Veronika (Universitas Sebelas Maret, 2024)
The Anggara Kasih tradition ceremony is one of the local cultures which still carried out today because there are local wisdom values in it. This study aims to explain the local wisdom values that exist in the Anggara Kasih Patirtan Cabean Kunti tradition and its relevance as Javanese teaching material in junior high school on the basic competencies of analyzing descriptive texts about regional traditional ceremonies. The data obtained in this research is qualitative data in the form of interviews. The sampling technique used in this research is snowball sampling. Data collection was done with three techniques, namely observation, interview, and document analysis. The technique used for validity testing is triangulation of data sources. The data analysis technique used the Miles and Huberman interactive model. The results of the research that have been conducted can be concluded as follows: (1) the local wisdom values contained in the Anggara Kasih tradition are: religious values, social values, cultural values, and environmental protection values; (2) the Anggara Kasih tradition carried out in Cabean Kunti village has relevance as teaching material in junior high school because it has four aspects, including: divine aspects, social aspects, cognitive aspects, and skills aspects. The results of this study are expected to be a reference for teachers to choose teaching materials about traditions that exist in their own area and be able to motivate students to study hard because they know firsthand the implementation of these traditions.